(untitled) - AMALIA, RISKA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Increasing of learning standart and graduating in national examination make learning education institution to be important. learning guidance institution is one effective way to help students to study. About increasing of kind and amount of learning education institution in surabaya, make parents who have fulfield life style more slective to choose good quality learning education institution. Goal of this researchis to know the effect of fulfield life style to decision making to using learning education istitution in south Surabaya. This research use quantitative approach with purposive sampling as many as 135 people who trust their children educated by four learning education institution in south Sirabaya which will be destination to distributing quetionare. With use data analisys regration simple linear. The rustl of thisresearch show tht fulfield life style has significnt influence to decision choose learning education institution service in south Surabaya with determination coeficient value 0,404. It has positive inluence which shown by positve determination value and medium category. It means morre positive fulfield life style, so influence to decision to choose learning education institution will increase. Keywords: Fulfield life style, decision of choosing service, learning education institution.